Design of Digital Library Prototype Using The Design Thinking Method - Miftahurrohmah Haque; Dwi Rosa Indah (Kresnamedia Publisher, 2022)
According to UNESCO (United Nations Educational, Scientific and Cultural Organization), Indonesian people's reading literacy interest has a literacy percentage of 0.001%, which means that out of 1.000 people, only one person likes to read. The digital reading movement attracts people's reading interest, especially with a digital library. Lahat District Library Service wants to re-establish a digital library that has been removed. By paying attention to usability and user experience, a digital library prototype design is carried out to develop the application to get user experience results with a good level of success and satisfaction. The method used is Design Thinking, which aims to design usable and valuable solutions by focusing on user needs. The results of the usability testing analysis of the digital library prototype created using the User Experience Questionnaire (UEQ) get